Effects of palm bunch ash and mycorrhiza on cucumber (Cucumis sativum L) performance on coarse-textured soil of Calabar, Southern Nigeria - Okechukwu Umunnakwe; Joyce Akpan; Francis Nwagwu; Edet Imuk; Bini Ebri (International Journal of Recycling of Organic Waste in Agriculture)
Purpose To evaluate the effect of palm bunch ash and mycorrhiza on soil properties and the performance of cucumber in Calabar.Method Factorial combination of five levels of palm bunch ash – PBA (0, 3, 6, 9 and 12 t/ha) and two mycorrhiza treatments (inoculated and non-inoculated), laid out in randomized complete block design (RCBD) with three replications. Data were collected on crop growth and yield indices, soil properties (physical, chemical and biological) each year, then combined and analyzed. Duncan’s Multiple Range Test (DMRT) at 5% probability was used to compare the means.Results There was increase in soil pH, organic carbon, phosphorus, potassium, calcium and magnesium as a result of PBA and mycorrhiza applications. PBA, mycorrhiza and their interactions significantly (p <.0. 05) influenced the vegetative growth and fruit yield of cucumber. Cucumber treated with 12 t/ha PBA had the highest vegetative growth and fruit yield values, which however were similar with those obtained from cucumber treated with 9 t/ha of PBA. Cucumber inoculated with mycorrhiza had superior growth and fruit yield than non-inoculated cucumber. The interaction of mycorrhiza and 12 t/ha PBA produced the highest values of vegetative growth and fruit yield indices, though similar with the interaction of mycorrhiza and 9 t/ha PBA.Conclusion Palm bunch ash was sufficient at 9 t/ha and is therefore recommended with mycorrhiza for effective soil nutrient enhancement and optimum cucumber production in Calabar.